Barriers to Prevention and Treatment of Type 2 Diabetes Mellitus Among Outpatients in Belarus - Sachkouskaya, Anastasiya; Sharshakova, Tamara; Kovalevsky, Dmitry; Rusalenko, Maria; Savasteeva, Irina; Goto, Aya; Yokokawa, Hirohide; Kumagai, Atsushi; Takahashi, Jumpei (Frontiers in Clinical Diabetes and Healthcare, 2022)
Objectives: This study aimed to determine the main barriers and reasons for non-adherence to preventive measures and treatment for type 2 diabetes mellitus among outpatients in Belarus. Methods: An anonymous questionnaire survey was conducted with 814 adults aged 18 years and over who visited outpatient health care units and hospitals in Belarus. The questionnaire was developed to analyze the perceived barriers that limit adherence to preventive measures and treatment for type 2 diabetes mellitus. Results: The proportion of respondents who reported doing daily physical activity was 53.2%, and 46.6% consumed at least 400 grams of fruit and vegetables per day. Among the 42.8% of respondents with a prescribed treatment for type 2 diabetes mellitus, 50.1% sometimes forgot to take their medicine. The specific barriers to treatment most frequently identified by survey respondents were “Financial situation” (23.5% of respondents), and “Fear of side effects” (25.2%). Those for lifestyle instructions were “Insufficient knowledge” (29.3%), “Financial situation” (27.9%), and “Lack of motivation” (21.7%). Conclusions: The study revealed that the main barriers to adherence were insufficient knowledge of diabetes mellitus and its treatment and an underestimation of the role of behavioral risk factors in health, combined with financial difficulties. We recommend raising awareness of behavioral risk factors for type 2 diabetes mellitus and the importance of adhering to preventive measures and treatment among patients in Belarus.